Capital Requirements for Latin American Banks in Relation to their Market Risks: The Relevance of the Basle 1996 Amendment to Latin America - Andrew Powell; Veronica Balzarotti (Inter-American Development Bank, Office of the Chief Economist, 1997)
Banks` market or `trading` risks have increased noticeably over the past years, largely as a result of the growth of liquid assets on banks` balance sheets and the increase in banks` off-balance sheet activities. Well-publicized bank failures and significant capital losses have focussed further attention on these developments. In January 1996, the Basle Committee recommended the imposition of capital charges related to banks` trading risks, and the European Community`s Capital Adequacy Directive (CAD) came into force on January 1st, adopting, in part, the Basle Amendment. The G10 countries are committed to full implementation of these recommendations by the end of 1997. This paper reviews the main features of the Basle Amendment, which allows banks a choice between a `standardized methodology` and the use of their own internal models, subject to the authorization of the relevant supervisor and a set of parameter values. The relevance of this regulation for Latin America is analysed in the light of the region`s characteristics. We suggest that these characteristics increase rather than diminish the importance of the implementation of market risk capital requirements in Latin America.
Keywords: 330